Efektivitas Pendaftaran Online Peserta Menggunakan Aplikasi Mobile- JKN dalam Pelayanan Pasien Rawat Jalan di RSU Mitra Medika Amplas - Chintami Octavia; Eric Winarno (Universitas Muhammadiyah Manado, 2024)
Health sector reform aims to enhance access and effectiveness of medical services for all communities. This study evaluates the impact of online registration via Mobile-JKN on outpatient services at RSU Mitra Medika Amplas in 2024. The research employs a quantitative approach with an analytical survey using a cross-sectional design. Respondents consist of 91 outpatients, selected through Purposive Sampling. Data analysis was conducted using Logistic Regression. Logistic regression analysis reveals that the OTP code plays a crucial role in the effectiveness of BPJS online registration, with an Odds Ratio (OR) of 15.221, meaning that patients who understand how to use the OTP code have 15.221 times higher chances of successful registration. In conclusion, user knowledge, internet network, and OTP code significantly affect patient services. RSU Mitra Medika is recommended to expand education and promotion of Mobile-JKN, optimize its utilization, and reduce queues at BPJS offices to improve service efficiency.